Differences in lower-body neuromuscular performance characteristics between three professional levels of men's basketball competition - Cabarkapa, D.; Cabarkapa, D. V.; Johnson, Q. R.; Philipp, N. M.; Fry, A. C. (The Journal of Strength and Conditioning Research, 2025)
While physical and physiological qualities that contribute to optimal on-court performance have been well-examined at the amateur level of basketball competition, they remain under-studied at the professional level of play. Thus, the purpose of this study was to examine differences in lower-body neuromuscular performance characteristics between 3 professional basketball leagues in Europe (i.e., ProA—Adriatic League; ProB—first national league; ProC—first regional league). Thirty-five athletes volunteered to participate in the present investigation. While standing on a uniaxial force plate system sampling at 1,000 Hz, each athlete performed 3 maximum-effort countermovement vertical jumps (CVJ) with no arm swing. One-way analysis of variance was used to examine between-level differences in force-time metrics within both the eccentric and concentric phases of the CVJ (p < 0.05). The findings reveal the presence of multiple phase-specific differences between the 3 competitive levels. ProB athletes demonstrated higher eccentric peak velocity and eccentric peak and mean power than their ProC counterparts. ProA athletes revealed notably higher concentric mean and peak force and power production capabilities when compared with ProC athletes, including higher jump height and reactive strength index-modified. Overall, these results suggest superior stretch-shortening cycle performance in athletes competing at a higher level of professional basketball play, further supporting the importance of well-designed and implemented resistance training regimens targeted toward optimizing strength and power development.